2007
DOI: 10.1016/j.molbiopara.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression of Cryptosporidium parvum glycoprotein gp40/15 in Toxoplasma gondii

Abstract: Cryptosporidium is a cause of diarrheal disease worldwide. Parasite glycoproteins involved in invasion of Cryptosporidium into host cells have been investigated as possible targets for effective interventions against this parasite. One of these, Cpgp40/15, is expressed as a precursor protein that is cleaved by a parasite-derived furin-like protease activity into gp15, a glycophosphatidyl inositol anchored surface protein, and gp40, that associates with gp15 and binds to host cells. Investigation of the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…gp40 is localized at the surface and the apical region of the parasite and is shed from the surface, while gp15 is on the surface of sporozoites and is shed in trails during gliding movement (135,172). Proteins present in the trails of gliding zoites have been shown to play a role in parasite attachment, invasion, and motility (133,172,201,(212)(213)(214)(215). In C. parvum, gp15 is attached to the membrane via a GPI anchor (216).…”
Section: Adherence Factorsmentioning
confidence: 99%
“…gp40 is localized at the surface and the apical region of the parasite and is shed from the surface, while gp15 is on the surface of sporozoites and is shed in trails during gliding movement (135,172). Proteins present in the trails of gliding zoites have been shown to play a role in parasite attachment, invasion, and motility (133,172,201,(212)(213)(214)(215). In C. parvum, gp15 is attached to the membrane via a GPI anchor (216).…”
Section: Adherence Factorsmentioning
confidence: 99%
“…n.a. (Nelson et al 2006) GP40/15 Glycoproteins that have a predicted 60 kDa precursor that is proteolytically cleaved into a 15 and 40 kDa protein probably by a subtilisin-like serine protease (CpSUB1); the GP60 locus is a highly polymorphic cluster and can be divided in two allelic groups Ia-Id (C. hominis), II (C. parvum); GalNAc-specific lectins such as HPA, AIA, and MPA prevent cell attachment and invasion indicating GPs might bind via GalNAc to cells; moreover Nac could reduce binding of the mAb against GP15 but not glucose, mannose or galactose; immunization of mice with mAb against GP15 could reduce oocyst shedding by 67.5%; GP15/GP40 are shed during gliding GP40: predicted N-terminal signal peptide, a polyserine domain, multiple predicted glycosylation sites, a single potential N-glycosylation site GP15: glycosylated, GPI anchor GP15 is localized on the surface of sporozoites and merozoites; GP40 is localized in the apical region whereas GP15 is found on the complete surface; since GP40 does not have a transmembrane domain or GPI anchor it is proposed that GP15 and GP40 form a complex (Tilley et al 1991;Jenkins et al 1993;Cevallos et al 2000a, b;Sestak et al 2002;O'Connor et al 2003O'Connor et al , 2007aWanyiri et al 2009Wanyiri et al , 2007 GP900 Ab against GP900 or subdomains reduced infection of cells in a concentration-dependent manner; GP900 mRNA levels peak at 14-26 h p.i. of cells; comparison of Ab reactivity between C. parvum and C. hominis against GP900 revealed that Ab did not cross-react between the species, indicating that morphological differences of surface molecules might account for species-specific infectivity Mucin-like glycoprotein composed of distal cysteine-rich domains separated by polythreonine domains and a large membrane proximal N-glycosylated core region; deglycosylated protein app.…”
Section: Calcium Is An Important Messengermentioning
confidence: 99%
“…Some of these contain core O-glycans such as terminal GalNAc␣1-Ser/Thr and/or Gal␤1a3GalNAc␣1-Ser/Thr, the so-called "Tn and T antigens" which are not normally exposed in mammalian cells because they are masked by additional sugars such as sialic acid (11). This had resulted in difficulties in generating appropriately glycosylated recombinant proteins, but this problem was overcome by heterologous expression of Cryptosporidium glycoproteins in T. gondii (55,57) which utilizes similar enzymes for O-glycosylation (74). The T. gondii system has also been used for genetic complementation approaches (73).…”
Section: Cryptosporidiummentioning
confidence: 99%